ANALISIS PENGARUH WORKING CAPITAL TURNOVER TERHADAP PROFITABILITAS DENGAN LIKUIDITAS SEBAGAI VARIABEL INTERVENING - Minar Savitri, Dhian Andanarini (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
This study aimed to assess the influence of WCT, and liquidity toward profitability of manufacturing companies in Indonesia Stock Exchange. Sampling was carried out using non-probabilistic sampling and obtained 62 of 149 manufacturing companies which are listed in Indonesia Stock Exchange in 2009-2012. The results of regression analysis show that WCT, have a significant effect toward liquidity. Meanwhile, the liquidity variable influence significantly toward the profitability.